Electromyographic diagnosis of the carpal tunnel syndrome - K. Toyonaga; C. R. de Faria (Arquivos de Neuro-Psiquiatria)
Sensory conduction velocities of the median nerVe were studied from digit to palm and from palm to wrist in normal subjects and in patients with the carpal tunnel syndrome. Definite slowing was noted in the palm to wrist segment, even in the early carpal tunnel syndrome. It was noted that 37% of normal women over 40 years of age had electrophysiological evidence of the carpal tunnel syndrome.